2018
DOI: 10.1016/j.actamat.2018.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Spall strength dependence on grain size and strain rate in tantalum

Abstract: We examine the effect of grain size on the dynamic failure tantalum during laser-shock compression and release and identify a significant effect of grain size on spall strength,which is opposite the prediction of the Hall-Petch relationship: monocrystals have a higher spall strength than polycrystals, which, in turn, are stronger in tension than ultrafine grain sized specimens. Post-shock characterization reveals ductile failure which evolves by void nucleation, growth, and coalescence. Whereas in the monocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(36 citation statements)
references
References 84 publications
3
29
0
3
Order By: Relevance
“…One-micrometer-thick polycrystalline Cu films were vacuum-deposited on <100>-oriented 500-nm-thick amorphous Si 3 N 4 substrates. High strain rate material properties are dependent on microstructure ( 36 ); thus, the samples were characterized in detail with electron microscopy. Sample thicknesses were confirmed, and grains were columnar ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-micrometer-thick polycrystalline Cu films were vacuum-deposited on <100>-oriented 500-nm-thick amorphous Si 3 N 4 substrates. High strain rate material properties are dependent on microstructure ( 36 ); thus, the samples were characterized in detail with electron microscopy. Sample thicknesses were confirmed, and grains were columnar ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been concluded that as the tensile stress field during spallation is almost entirely isotropic, the voids in ductile materials tend to become almost perfectly spherical (3,31,46). However, the opposite has also been suggested by Remington et al (36) for nanocrystalline Ta-that spall-induced voids would have an oblate spheroid shape as spall is primarily intergranular in nanocrystalline Ta samples.…”
Section: Quantification Of Void Evolution During Spallmentioning
confidence: 94%
“…Consequently, the vast majority of literature has been devoted to computational modeling efforts of simulated microstructures [18][19][20][21][22][23][24][25][26][27][28][29][30][31] . With regard to the limited experimental studies, the work has utilized laser-driven compression of physically deposited thin films or electrodeposits (<500 µm) 32 . Within that subset, the number of laser-based studies presenting post-mortem microstructural characterization is limited to just a few (e.g., 33,34 ).…”
mentioning
confidence: 99%
“…Nevertheless, HPT has an important advantage because experiments on a magnesium alloy showed that it is generally feasible to conduct HPT processing at a relatively lower temperature than ECAP, including at room temperature (RT), because of the large hydrostatic pressure that is imposed on the sample during the processing operation. [21] For refractory metals, reports are now available on the processing of W by ECAP or HPT over a range of temperatures from 673 to 1273 K, [22][23][24][25] the processing of Ta by ECAP at RT [26][27][28][29][30][31] or at 1173 or 1473 K [32] and HPT at RT, [33][34][35][36][37] the processing of V by HPT at RT, [38][39][40] and the processing of Mo by ECAP or HPT at temperatures from 623 to 1073 K [41][42][43][44][45][46][47][48] and HPT at both RT [38,[49][50][51][52][53][54][55][56][57] and a cryogenic temperature of 80 K. [54,56] Although several reports are now available on the processing of Mo by HPT, there have been no systematic studies of the concurrent evolution of microstructural refinement and hardness in pure molybdenum as are available, for example, in conventional fcc metals such as aluminum, …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, HPT has an important advantage because experiments on a magnesium alloy showed that it is generally feasible to conduct HPT processing at a relatively lower temperature than ECAP, including at room temperature (RT), because of the large hydrostatic pressure that is imposed on the sample during the processing operation . For refractory metals, reports are now available on the processing of W by ECAP or HPT over a range of temperatures from 673 to 1273 K, the processing of Ta by ECAP at RT or at 1173 or 1473 K and HPT at RT, the processing of V by HPT at RT, and the processing of Mo by ECAP or HPT at temperatures from 623 to 1073 K and HPT at both RT and a cryogenic temperature of 80 K …”
Section: Introductionmentioning
confidence: 99%